DAUROH NAHWU 10 HARI UNTUK MENINGKATKAN KEMAMPUAN ILMU BAHASA ARAB BAGI MAHASISWA PRODI PENDIDIKAN BAHASA ARAB, UNIVERSITAS NEGERI MAKASSAR - Ahmad Sirfi, Ahmad Sirfi Fatoni; Irfan; Rahmat Rizal; Hadyan Hashfi MS; Mudrik Minanurrohman (Jurnal Abdi Masyarakat Pendidikan, 2025)
This article aims to examine a 10-day nahwu service program to improve Arabic language skills for students majoring in Arabic Language Education at State University of Makassar. This service program was motivated by the low level of proficiency in nahwu among the majority of students majoring in Arabic Language Education. Sometimes, community service volunteers hold informal discussions related to this subject both in and outside the classroom, but it is still common to find students who do not know about this subject. The background of the type of Islamic boarding school also affects students' abilities in nahwu. The community service methods used include two stages, namely the Preparation stage and the Implementation stage. The preparation stage included several things, namely: Preparation of the community service proposal, Preparation of materials, and Preparation of training facilities and infrastructure. Meanwhile, the implementation stage included: an Initial introduction to the program and its rules, the Beginning stage of the dauroh training, the Training evaluation stage, and the Mentoring stage. Some of the results of the program included: (1) The participants were very enthusiastic in participating in the nahwu dauroh program. They all received certificates from the training activity if they met the specified criteria; (2) The use of the book Matnu al-Ajurumiyyah by Muhammad bin Muhammad bin Dawud al-Shonhaji has successfully improved the participants' knowledge of Arabic grammar. This is because the book contains material that is easy to understand, relevant, systematic, and concise; (3) After the implementation of the nahwu program, there was an improvement in the participants' abilities, from a previous average score of 77.28 to a final score of 91.71.